THE DESIGN OF MULTI LOCATION INTERNET OF THINGS HYDROPONIC CONTROL SYSTEM - Lestari, Qori
As a solution for agricultural land scarcity, a long distance internet of things hydroponic farm control system is made in this research. The hydroponic kits are located at two locations, Cisitu and Padasuka. Both of them are located in Bandung, and located 5.5 kilometers from each other. Hydroponic control system sends sensor datas to the server through the internet. Data that are being sent to the server are water flow rate, ambient temperature, ambient humidity, water temperature, pH value, and electrical conductivity. The system also captured a digital image of a sample plant and send it to the server. Electrical conductivity value from the water in the hydroponic kit is also used as a feedback on closed-loop proportional control system for automated nutrient dosing. With this long distance hydroponic control system, this system can do monitoring on hydroponic kit conditions located in two different locations, regularly sends data from hydroponic kit, keeps the electrical conductivity value of the water in the hydroponic kit at an ideal value, model the plant height growth from plant height data and hydroponic kit electrical conductivity value data, and shows growth trend, environmental conditions, and measured plant image on an interface.